Predicting the development of clinical arthritis in anti-CCP positive individuals with non-specific musculoskeletal symptoms: a prospective observational cohort study. Issue 9 (12th April 2014) - Rakieh, C; Nam, J L; Hunt, L; Hensor, E M A; Das, S; Bissell, L-A; Villeneuve, E; McGonagle, D; Hodgson, R; Grainger, A; Wakefield, R J; Conaghan, P G; et al.
Abstract : Objectives: To monitor progression to inflammatory arthritis (IA) in individuals with non-specific musculoskeletal (MSK) symptoms and positive anticyclic citrullinated peptide (anti-CCP) antibodies. To develop a pragmatic model to predict development of IA in this patient group. Methods: In this prospective observational cohort, patients with new non-specific MSK symptoms and positive anti-CCP were recruited from regional primary care and secondary care referrals. Clinical, imaging and serological parameters were assessed at baseline. Cox regression analysis was performed to identify predictors of progression to IA and develop a risk score to stratify patients at presentation. Findings: 100 consecutive patients (73 women, mean age 51 years) were followed up for median 19.8 months (range 0.1–69.0); 50 developed IA after a median 7.9 months (range 0.1–52.4), 34 within 12 months. The majority (43/50) fulfilled the 2010 American College of Rheumatology/European League Against Rheumatism criteria for rheumatoid arthritis. A model for progression to IA was devised using four variables: tenderness of hand or foot joints, early morning stiffness ≥30 min, high-positive autoantibodies, and positive ultrasonographic power Doppler signal. None of the five individuals at low risk (score 0) progressed to IA, compared with 31% of 29 at moderate risk (1–2) and 62% of 66 at high risk (≥3). Adding shared epitope increased the number at low risk (score 0–1; 0/11 progressed). Conclusions: In patients presenting with non-specific MSK symptoms and anti-CCP, the risk of progression to IA could be quantified using data available in clinical practice. The proposed risk score may be used to stratify patients for early therapeutic intervention. Trial registration number: NCT02012764 at ClinicalTrials.gov.